Glucocorticoid doses according to tissue/organ involvement in ANCA-associated vasculitis - Yaşar Bilge, Nazife Şule (Acta Medica, 2024)
Antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitides (AAV) are a group of disorders that include granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), renal-limited vasculitis, and eosinophilic granulomatosis with polyangiitis (EGPA). Infections and cardiovascular diseases are the main causes of death in patients with AAV. New treatment regimens with low-dose glucocorticoidsare proposed to reduce the frequency of side effects. Studies related to the use of glucocorticoids in AAV patients were searched in the literature and results were summarized. Low-dose steroid protocols are not inferior to standard dose treatment and have fewer side effects. Although their effectiveness appears to be similar and their side effects appear to be less, the long-term results of low-dose regimens should also be evaluated.New studies are needed for alternative treatment regimens.